Establishing specialized economic courts in Saudi Arabia to boost investments - ALBAHETH, Hamza E. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This paper seeks an effective mechanism to resolve economic disputes and economic crimes by first highlighting the absence of an effective legal platform to resolve such disputes and then suggesting remedial measures through the establishment of specialized economic courts. The author claims that this will offer a new mechanism for resolving economic disputes, in addition to the new commercial courts and the alternatives that already exists in the system. Such a step will also prove a cultural shift facilitating litigants and keeping them abreast with internal and external challenges faced in boosting foreign and domestic investments.RESUMEN Este documento busca un mecanismo efectivo para resolver disputas económicas y crímenes económicos destacando primero la ausencia de una plataforma legal efectiva para resolver tales disputas y luego sugiriendo medidas correctivas a través del establecimiento de tribunales económicos especializados. El autor afirma que esto ofrecerá un nuevo mecanismo para resolver disputas económicas, además de los nuevos tribunales comerciales y los medios alternativos que ya existen en el sistema. Tal paso también demostrará un cambio cultural que facilitará a los litigantes y los mantendrá al tanto de los desafíos internos y externos que enfrentan para impulsar las inversiones extranjeras y nacionales.